Hubungan Hypnoprenatal Massage terhadap Kesehatan Mental Ibu Hamil Trimester III - Annisa Amalia Hanifa; Melyana Nurul Widyawati; Suryati Kumorowulan; Djamaluddin Ramlan (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2022)
Pregnancy is a very vulnerable process in women's lives so that mental health problems often arise. Neglected mental health will result in a number of adverse consequences for both the mother and the fetus. Hypnoprenatal massage is a non-pharmacological therapy that is believed to be very effective for overcoming stress, increasing relaxation and affecting emotional status and psychosocial health. This study aims to analyze the effect of hypnoprenatal massage on improving mental health of pregnant women in the third trimester. This study is nonrandomized control group pretest-posttest conducted in Semarang Regency at five primary healthcares. This study used 36 respondents who were divided into intervention and control groups. The intervention group got hypnoprenatal massage given for 2 weeks while the control group got standard care of third trimester. Mental health measure using the Self Reporting Questionnaire (SRQ) before and after treatment. Based on the result of this study there was a decrease in the average SRQ score of 2.78 after receiving hypnoprenatal massage. Meanwhile, the SRQ score in control group decrease was only 0.56 with a p-value between the two groups of 0.004 (p-value<0.05). This study concludes that hypnoprenatal massage affects the improvement of mental health of pregnant women in the third trimester. Keywords: hypnosis, prenatal massage, mental health